WPŁYW ZOBOWIĄZANIA DO NAPRAWIENIA SZKODY NA EFEKTYWNOŚĆ INSTYTUCJI WARUNKOWEGO UMORZENIA POSTĘPOWANIA KARNEGO - Juszka, Karol (Zeszyty Prawnicze, 2016)
The Effect of a Defendant’s Obligation to Redress Damage on the Effectiveness of Conditional Discontinuance of Criminal Proceedings Summary The aim of this article is to give a statistical presentation of the theoretical and practical aspects of a defendant’s obligation to redress damage in a verdict involving discontinuance of criminal proceedings. My observations are based on a statistical analysis of data I collected for 405 cases involving conditional discontinuance of criminal proceedings and the effectiveness of such verdicts. The cases were heard in the Kraków Regional Court (Sąd Okręgowy w Krakowie) and the district courts (sądy rejonowe) within its area of jurisdiction. For the statistical analysis I used the Spearman one-way ANOVA model, the Mann-Whitney U test, and the Kruskal-Wallis test to calculate the correlation coefficient. My analysis also includes a set of legislative proposals, both for the modification of the statutory construction of the institution of conditional discontinuance of proceedings in Polish criminal law, as well as for the practical application of the existing provisions.<br style="font-style: normal; font-variant: normal; font-weight: normal; letter-spacing: normal; line-height: normal; orphans: 2; text-align: -webkit-auto; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-size-adjust: auto; -webkit-text-stroke-width: 0px;" /><br style="font-style: normal; font-variant: normal; font-weight: normal; letter-spacing: normal; line-height: normal; orphans: 2; text-align: -webkit-auto; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-size-adjust: auto; -webkit-text-stroke-width: 0px;" />